1988
DOI: 10.2337/diacare.11.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Diet Therapy for Minority Patients With Diabetes

Abstract: Diet therapy for minority diabetic patients must be directed to NIDDM, the most prominent form of diabetes in minority populations. Diet programs must be tailored to the cultural framework, and traditional foods with desirable characteristics can be encouraged. To teach patients about diet, educators must use educational techniques appropriate to culture and literacy of the patient and family. Single-concept messages such as "eat less fat" or "eat less food" promote learning and minimize failure. Nutrition inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Overall, those who primarily spoke Cantonese or Portuguese were less likely to utilize many of the listed resources and less likely to utilize a variety of resources. One reason for this may be that many resources are not culturally appropriate or available in their language, thereby creating a barrier to accessing resources [41].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, those who primarily spoke Cantonese or Portuguese were less likely to utilize many of the listed resources and less likely to utilize a variety of resources. One reason for this may be that many resources are not culturally appropriate or available in their language, thereby creating a barrier to accessing resources [41].…”
Section: Discussionmentioning
confidence: 99%
“…While more culturally-specific materials and materials in other languages are still needed, there has been an increased awareness of this need over the past 15 years [70,71], particularly for Spanish-speaking patients. Education designed to be culturally specific has been shown to increase patient satisfaction and promote behavior change in lifestyle modification programs [72].…”
Section: Cultural Awarenessmentioning
confidence: 99%
“…One of the few studies that examined this question indicated that when dietary advice was the sole treatment, it appeared to have no effect on the metabolic control of the patients 10 . It has been suggested that nutrition therapy for black patients is unsuccessful when the diet prescription does not relate to the patient's cultural environment and economic situation, and is presented in ways that are difficult for low-literacy patients to understand and implement 11 . To date there is a paucity of data on dietary intake and practices and dietary advice given to black type 2 diabetic patients who attend primary health-care services in South Africa.…”
mentioning
confidence: 99%